2019
DOI: 10.3390/molecules24081490
|View full text |Cite
|
Sign up to set email alerts
|

A Useful Synthesis of 2-Acylamino-1,3,4-oxadiazoles from Acylthiosemicarbazides Using Potassium Iodate and the Discovery of New Antibacterial Compounds

Abstract: A useful method for the synthesis of 2-acylamino-1,3,4-oxadiazoles was developed. By using potassium iodate as an oxidant in water at 60 °C, a wide range of 2-acylamino-1,3,4-oxadiazoles were afforded in moderate to excellent yields within two hours. This method could provide a facile shortcut to generate a series of 2-acylamino-1,3,4-oxadiazoles in medicinal chemistry. Interestingly, some highly potent antibiotic compounds were found through this synthetic method, and some of them displayed a significant impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, in case of antifungal activity compound 60 found to be most active against C. albicans (MIC = 12.5 µg/mL) and compound 57 displayed better activity against all tested fungal strains (MIC range = 25-50 µg/mL) (Table 25). Active compounds (57)(58)(59)(60) showed almost similar activity as compared to standard drugs Ciprofloxacin and Fluconazole (Table 25) [67]. subtilis.…”
Section: Antibacterial and Antifungal Activities Of 25-disubstituted-...mentioning
confidence: 89%
See 1 more Smart Citation
“…However, in case of antifungal activity compound 60 found to be most active against C. albicans (MIC = 12.5 µg/mL) and compound 57 displayed better activity against all tested fungal strains (MIC range = 25-50 µg/mL) (Table 25). Active compounds (57)(58)(59)(60) showed almost similar activity as compared to standard drugs Ciprofloxacin and Fluconazole (Table 25) [67]. subtilis.…”
Section: Antibacterial and Antifungal Activities Of 25-disubstituted-...mentioning
confidence: 89%
“…SAR data revealed that introduction of electron donating group CH 3 and electron withdrawing NO 2 at para position of phenyl ring attached to 1,3,4-oxadiazole ring improved the antibacterial activity of compounds except against E. coli. Compounds(28)(29)(30) showed very less potency as compared to Levofloxacin (Table15)[58] Guo et al (2019). evaluated antibacterial activity of Norfloxacin and 1,3,4-oxadiazoles hybrids against methicillin-resistant Staphylococcus aureus (MRSA).…”
mentioning
confidence: 99%
“…Moreover, a new series of 2-acylamino-1,3,4-oxadiazole derivatives was developed by Li et al (2019). Compound 22a (Figure 9) appeared to be most active against Staphylococcus aureus (MIC = 1.56 µg/mL), while 22b and 22c (Figure 9) were most effective against Bacillus subtilis (MIC = 0.78 µg/mL); levofloxacin was used as a positive control [55]. Several conclusions regarding the structure-activity relationship can be drawn from the discussed derivatives.…”
Section: Antibacterial Activity Of Amino Derivatives Of 134-oxadiazolementioning
confidence: 99%
“…Tianlei and co‐workers developed a method for the synthesis of biologically important 2‐acylamino‐1,3,4‐oxadiazole 122 by using KIO 3 as a mild oxidant (Scheme 22). [81] This method was found to be facile, and less time consuming. The mechanism proposed by the authors suggested that the generation of carbodiimide intermediate via release of sulfur dioxide from keto‐ enol form of thiosemicarbazide 121 by KIO 3 ‐mediated oxidation.…”
Section: Non‐metal‐assisted Desulfurizationmentioning
confidence: 99%